Challenger Treatment of Various Cancers with T Cells Engineering - Heidari Alireza; Locci Elena; Raymond Silvia; Gobato Ricardo (Journal of Lung Cancer Epidemiology, 2023)
Through T-cell engineering, researchers at the California South University (CSU) Cancer Research Institute (CRI) have shown that tumor growth can be stopped in a variety of cancers and prevented from spreading to other tissues. Findings from this study are the result of decades of research by Professor Ph.D. A. Heidari and our team of CSU, who discovered a protein called AH that can inhibit the growth and spread of cancer cells in several different ways. They become in the tissues of the body. The T cells were armed with MDA-7/AH to target cancer more widely. The engineering of T cells to produce MDA-7/AH causes cancer cells to be destroyed regardless of the expression of the target molecules. The tumor site is often very hostile to immune cells. It was found in the research that MDA-7/AH can help T cells proliferate and increase the number of cancer cells. The T cells were armed with MDA-7/ AH to target cancer more widely. The engineering of T cells to produce MDA-7/AH causes cancer cells to be destroyed regardless of the expression of the target molecules. The tumor site is often very hostile to immune cells. We discovered that MDA-7/AH can help T cells proliferate and increase the number of cancer cells.
Keywords: Cancer